Motywy tematyczne we współczesnych przemówieniach funeralnych - Cieśla, Bartłomiej (Stylistyka, 2020)
The aim of the article is to present thematic motifs that appear in funeral speeches given by lay people. These speeches have the form of a one-sided narration, shaped to create the best possible picture of the deceased. The author analyses seven contemporary funeral speeches which were recorded during funeral ceremonies while saying farewell to deceased Polish politicians. The speeches discussed are characterized by a considerable degree of concentration on the achievements of the deceased. Focusing on deeds – especially in laudation – is a way of cementing the memory of a person who has influenced a certain community. The funeral speech, as a genre pattern, performs the function of sustaining memory about a particular person, whose picture acquires the form of a tendentious, deformed verbal monument. It does not only present the figure of the deceased, but also evaluates their achievements in an individual and collective dimension. The assessment in both cases is designed by the speaker and is often detached from the real social feelings. The speeches under analysis are a type of occasional speeches with not only invariant stylistic and structural features (which have been pointed out in scientific or advisory literature many times), but also invested with standard and repetitive thematic threads.